A HISTÓRIA DA PRODUÇÃO DAS VACINAS DA COVID-19 NO BRASIL: UMA REVISÃO SISTEMÁTICA - Raelle Cordeiro, Wdylane (Revista Multidisciplinar do Nordeste Mineiro, 2023)
Brazil began the search for vaccines against COVID-19 through agreements with different vaccine manufacturers at an international level, such as AstraZeneca, Pfizer, Coronavac (produced by the Butantan Institute in partnership with Sinovac) and the Covax Facility, an initiative global initiative to ensure equitable access to vaccines. In January 2021, the National Health Surveillance Agency (Anvisa) granted emergency use authorizations for the Coronavac and AstraZeneca/Oxford vaccines. Later, other vaccines, such as Pfizer, also received approval for emergency use. Through a bibliographical review, it can be concluded that the process of producing and distributing vaccines in Brazil involved logistical and political challenges, including debates about the effectiveness and safety of vaccines, acquisition of inputs for production, distribution to states and delays in the.